2003
DOI: 10.1093/gerona/58.7.b598
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restriction and Beta-Cell Sensitivity to Glucose in Adult Male Rhesus Monkeys

Abstract: We examined the effects of dietary restriction (DR) and age on ss-cell function and peripheral insulin sensitivity in rhesus monkeys. A semipurified diet was provided either ad libitum for approximately 8 hours/day to controls (C) or as approximately 70% of baseline intake to restricted (R) animals for 10 years. The minimal model of C-peptide secretion and kinetics and the labeled 2-compartment minimal model of glucose kinetics were identified using plasma glucose, C-peptide, and insulin concentrations during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…Two studies of CR in rhesus monkeys have been ongoing for the past 20 years, involving levels of restriction of 30% less than ad libitum feeding. As expected, CR resulted in decreased body fat and temperature (Lane et al, 1996) improved glucose tolerance, delayed T-cell senescence (Gresl et al, 2003;Messaoudi et al, 2006). Notably, these studies revealed a marked effect of CR in suppressing the occurrence of age-related disease, with CR monkeys having a three times lower incidence of age-related disease (Colman et al, 2009).…”
Section: Cr In Primatessupporting
confidence: 67%
“…Two studies of CR in rhesus monkeys have been ongoing for the past 20 years, involving levels of restriction of 30% less than ad libitum feeding. As expected, CR resulted in decreased body fat and temperature (Lane et al, 1996) improved glucose tolerance, delayed T-cell senescence (Gresl et al, 2003;Messaoudi et al, 2006). Notably, these studies revealed a marked effect of CR in suppressing the occurrence of age-related disease, with CR monkeys having a three times lower incidence of age-related disease (Colman et al, 2009).…”
Section: Cr In Primatessupporting
confidence: 67%
“…The UW study assessed glucose kinetics during an intravenous glucose tolerance test. Compared to controls, DR monkeys had lower basal ␤-cell sensitivity to glucose, greater insulin sensitivity and a lower first-phase plasma insulin response [17]. Body fatness was highly predictive of glucose response in these monkeys, and these factors may contribute to an overall reduced disease risk.…”
Section: Glucose Insulin and Metabolic Ratementioning
confidence: 89%
“…Modeling of pre- and posthepatic insulin secretion by concurrent measurement of glucose, C-peptide, and insulin levels indicated that in CR monkeys the pancreatic beta cell is less sensitive to glucose in the fasted state but not in the glucose-stimulated condition. Differences between groups are related to differences in (abdominal) body fatness (Gresl et al 2003a). CR increased insulin receptor signaling as evidenced by greater IRS-1 and -2 protein abundance.…”
Section: Aggregated Observationsmentioning
confidence: 99%